A novel enhanced ammonia-water power/cooling cogeneration system with dual level cooling temperature: Thermodynamic and economic assessments. (15th September 2021) - Mosaffa, A.H.; Garousi Farshi, L.; Khalili, S.
Highlights: An enhanced ammonia-water CCP is introduced and analyzed thermoeconmically. Dual level cooling temperature is achieved by utilizing an ejector. Optimized energy and exergy efficiencies are obtained 68.8 % and 37 %, respectively. The simple payback period is approximately 4.8 years. Abstract: The present study proposed and investigated a novel parallel combined cooling and power (CCP) system using the ammonia–water solution as a working fluid. The major advantage of this system is employing two evaporators to produce cooling in dual level cooling temperatures and capacities. To produce high-temperature refrigeration output, an ejector refrigeration loop is introduced. Moreover, the power generation subsystem is employed between absorber and rectifier to recover of ammonia content in the vapor exiting the turbine for refrigeration. To prediction of ejector performance, a new model is proposed based on the shock circle model. To find the effect of key parameters on the system performance, the system is analyzed thermo-economically. The parametric study results show that high-temperature cooling load has the biggest effect on both thermodynamic and economic performance. Moreover, a parametric optimization is conducted and the optimized system is compared with several ammonia-water CCP systems in the literature. The comparison results show a significant enhancement in thermodynamic performance. In this case, the optimal energy efficiency of 68.8 %, exergy efficiency of 37 % and cooling-to-power ratio of 8.77 are estimated. From economic analysis, the optimal net present value and simple payback period are obtained by 49.2 M and 4.8 years, respectively.